Digital Governance in Transition: A Narrative Review of E-Government Implementation - Mambang (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
E-government is a major transformation in public administration. It integrates information and communication technology to improve efficiency, transparency, and citizen engagement. This narrative review examines the implementation of e-government and its impact on public service transformation across diverse contexts. Literature was systematically collected from databases including Scopus, Web of Science, Google Scholar, and PubMed, using keywords such as e-government, digital governance, citizen engagement, public service transformation, and transparency. Inclusion criteria emphasized peer-reviewed studies from 2010–2024 focusing on digital governance and public administration. Studies were screened, evaluated, and synthesized thematically. Findings reveal that emerging technologies, notably artificial intelligence, the Internet of Things, and blockchain, significantly improve service delivery efficiency and data security. Case studies from Estonia and Russia highlight successful adoption models, while experiences in Indonesia and other developing countries reveal persistent challenges related to infrastructure, literacy, and governance capacity. Public trust and citizen participation were found to be critical determinants of adoption, shaped by digital literacy, data security perceptions, and cultural attitudes. The discussion emphasizes systemic barriers—political resistance, legal rigidity, and cultural mistrust—that impede adoption, alongside strategies such as strong digital leadership, adaptive legal frameworks, and investment in digital literacy. This review concludes that while e-government has substantial potential to transform public service delivery, its success depends on aligning technological innovation with systemic reform and citizen engagement. Future research should incorporate interdisciplinary approaches, citizen perspectives, and longitudinal analyses to better understand and sustain digital transformation.